Spatial coherence and the persistence of high diversity in spatially heterogeneous landscapes - Ankit Vikrant; Susanne Pettersson; Martin Nilsson Jacobi (Ecology and Evolution, 2022)
Abstract Our planet hosts a variety of highly diverse ecosystems. The persistence of high diversity is generally attributed to factors such as the structure of interactions among species and the dispersal of species in metacommunities. Here, we show that large contiguous landscapes—that are characterized by high dispersal—facilitate high species richness due to the spatial heterogeneity in interspecies interactions. We base our analysis on metacommunities under high dispersal where species densities become equal across habitats (spatially coherent). We find that the spatially coherent metacommunity can be represented by an effective species interaction‐web that has a significantly lower complexity than the constituent habitats. Our framework also explains how spatial heterogeneity eliminates differences in the effective interaction‐web, providing a basis for deviations from the area‐heterogeneity tradeoff. These results highlight the often‐overlooked case of high dispersal where spatial coherence provides a novel mechanism for supporting high diversity in large heterogeneous landscapes.